In silico and in vitro investigations of antihelmintic activities of selected approved drugs - Christopher Arinze Agube; Daniel Lotanna Ajaghaku; Ikemefuna Chijioke Uzochukwu (Archives of Community Medicine and Public Health - Peertechz Publications, 2020)
Objective: We investigated the binding affinities of some approved drugs to Ascaris suum Mitochondrial Rhodoquinol Fumarate Reductase (MRFR), an essential enzyme for ascaris survival, and the possibility of repurposing these drugs as antihelmintic agents using in silico molecular docking and in vitro paralysis and mortality times of fifteen selected front runners. Method: Two hundred approved drugs were selected from ZINC® database based on bioactivity scores while MRFR (PDB code, 3vra) was obtained from the Protein Data Bank (PDB). Both were prepared using AutoDock tools v.1.5.6 and Chimera v.1.9.The docking protocol was validated by computationally reproducing the binding of atpenin to MRFR. The selected approved drugs and the receptor were docked using AutoDockVina v. 4.0. The docking results were analyzed using PyMoL v. 1.4.1.The paralysis and mortality times of the identified frontrunners against Pheretima posthuma were determined in vitro and synergistic testings were done by the checkerboard method. Result: Fifteen drugs had binding free energies between -7.825 to -11.025 kcal/mol while four of these drugs (mefloquine, doxycycline, mepacrine and proguanil) emerged as major frontrunners by both in silico and in vitro assessments. The paralysis and mortality times of the four drugs were between 0.33-0.50 hr as against 1.80- 2.36 hr for albendazole. They were therefore predicted to have ability to affect MRFR in the same manner as atpenin hence, suggestive of potential antihelmintic activity. Conclusion: The antihelmintic potentials of mefloquine, doxycycline, proguanil and mepacrine have been demonstrated. In vivo investigation of these frontrunner drugs is strongly recommended.